Perilaku Merokok Siswa-Siswi Sekolah Menengah Pertama (SMP) di Wilayah Kerja Puskesmas Sei Agul Medan - Lubis, Sri Novita; Bukit, Dhani Syahputra (Jurnal Kesehatan, 2019)
Cigarettes are one of the tobacco products that contain addictive substances and other ingredients that are harmful to health both directly and indirectly. According to RisetKesehatanDasar (Riskesdas), there is a trend in the age of smoking that is increasingly young from year to year. This study aims to describe smoking behavior among students of junior high school in the working area of PuskesmasSeiAgul Medan. This research was a descriptive study with a cross-sectional study. The population of this study was all the male and female students in grade 8 of junior high school. There were a total of 384 samples. Data were collected with a questionnaire. The results showed that the prevalence of ever smoking was 32,6%. The respondents who have smoking habits was 85,6%. The highest number of consumption cigarettes was <1 cigarette per day (72,8%) and the lowest was 11-20 cigarettes per day (1,0%), 76,3% have a family history of smoking, and 58,1% had a smoking friend. A total of 98,2% of respondent have been exposed to cigarette advertisements and 63,3% often see cigarette advertisements. The average pocket money was Rp9.567,57. The average cost that spent on cigarettes was  Rp 3.473,68.